Mediation analysis - Iacobucci, Dawn. (Los Angeles, [Calif.] ; London : SAGE, 2008)
This text explores even the fundamental assumptions underlying mediation analysis and describes options for analyzing mediation data as well as providing syntax for a widely available and popular computer program so users can begin implementing mediation ideas immediately on their data.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: elektronické knihy; electronic books; Social sciences -- Mathematical models; Structural equation modeling; Regression analysis